Drug discovery of anticancer drugs targeting methylenetetrahydrofolate dehydrogenase 2. Issue 12 (December 2018) - Asai, Ayumu; Koseki, Jun; Konno, Masamitsu; Nishimura, Tatsunori; Gotoh, Noriko; Satoh, Taroh; Doki, Yuichiro; Mori, Masaki; Ishii, Hideshi
Abstract: Many anticancer drugs have serious adverse effects; therefore, it is necessary to target features specific to cancer cells to minimize the effects on healthy cells. Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) was reported to be specifically enhanced in cancer. We confirmed the validity of MTHFD2 as a drug discovery target using clinical data. In addition, we performed in silico screening to design an anticancer drug specifically targeting MTHFD2. Analysis of the clinical data indicated that MTHFD2 was enhanced in most cancers compared with normal tissues, and affected the prognosis in cancer patients. Candidate compounds for MTHFD2 inhibitors were identified using in silico drug discovery techniques, and the important interactions for MTHFD2 binding were determined. In addition, these candidate compounds decreased levels of MTHFD2 metabolites in cancer cells. The findings of the present study may help to develop anticancer drugs targeting MTHFD2, with a view to minimizing the adverse effects of anticancer drugs.